Pengaruh Praktik Kewirausahaan dan Literasi Keuangan terhadap Intensi Berwirausaha dengan Mediasi Efikasi Diri dalam Mata Kuliah Kewirausahaan Digital pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta - Magriba Nurul Rizki; Ari Saptono; Agus Wibowo (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the effect of entrepreneurship practice and financial literacy on students' entrepreneurial intention, both directly and through the mediating role of self-efficacy, within the Digital Entrepreneurship course at the Faculty of Economics and Business, Universitas Negeri Jakarta. A quantitative survey design was employed, involving 327 active students from the 2022 and 2023 cohorts selected through proportional random sampling from a population of 1,800 students. Data were analyzed using Partial Least Squares Structural Equation Modeling with the aid of SmartPLS software. The results show that entrepreneurship practice has no significant direct effect on entrepreneurial intention, whereas financial literacy does. Both independent variables, however, strongly predict self-efficacy, which in turn significantly influences entrepreneurial intention. Mediation testing further confirms that self-efficacy fully mediates the relationship between entrepreneurship practice and entrepreneurial intention, and partially mediates the relationship between financial literacy and entrepreneurial intention. These findings suggest that self-efficacy functions as a key mechanism through which practical experience and financial knowledge are translated into a stronger intention to start a business. This study enriches the Theory of Planned Behavior in digital entrepreneurship education, offering practical considerations for universities in designing learning that emphasizes hands-on practice and deliberately cultivates students' self-confidence and financial literacy.